Barriers and enablers to healthcare system uptake of direct oral anticoagulants for stroke prevention in atrial fibrillation: a qualitative interview study with healthcare professionals and policy makers in England - Medlinskiene, Kristina; Richardson, Susan; Petty, Duncan; Stirling, Katherine; Fylan, Beth (BMJ open, 2023)
ObjectiveTo better understand the factors influencing the uptake of direct oral anticoagulants (DOACs) across different health economies in National Health Service England from the perspective of health professionals and other health economy stakeholders.DesignQualitative interview study using a critical realism perspective and informed by the Diffusion of Innovations in Service Organisations model.SettingThree health economies in the North of England, United Kingdom.ParticipantsHealthcare professionals involved in the management of patients requiring oral anticoagulants, stakeholders involved in the implementation of DOACs and representatives of pharmaceutical industry companies and patient support groups.InterventionSemistructured interviews (face-to-face or telephone) were conducted with 46 participants. Interviews were analysed using the Framework method.ResultsIdentified factors having an impact on the uptake of DOACs were grouped into four themes: perceived value of the innovation, clinician practice environment, local health economy readiness for change, and the external health service context. Together, these factors influenced what therapy options were offered and prescribed to patients with atrial fibrillation. The interviews also highlighted strategies used to improve or restrict the uptake of DOACs and tensions between providing patient-centred care and managing financial implications for commissioners.ConclusionsThe findings contribute to the wider literature by providing a new and in-depth understanding on the uptake of DOACs. The findings may be applicable to other new medicines used in chronic health conditions.